Nature visits during the COVID-19 pandemic in Norway: Facilitators, motives, and associations with sociodemographic characteristics - Litleskare, Sigbjørn; Calogiuri, Giovanna (Frontiers in Public Health, 2023)
The COVID-19 pandemic has been linked to increased mental health issues and reduced well-being. Researchers also reports increased frequency of nature visits during the pandemic, proposing it may mitigate some of these negative consequences. Using the case of Norway, a country with ample access to nature and relatively low levels of pandemic-related restrictions, this study sought to i) understand how the COVID-19 crisis impacted patterns of nature visits and specific nature-based activities, ii) examine how these patterns varied among different population groups and levels of restrictions, and iii) explore the motives and facilitators for increased frequency of nature visits. The results indicated an increase in nature visits during the crisis, particularly among individuals exposed to long-term restrictions, women, younger respondents, and individuals with high-income households. The main facilitators for increased frequency of nature visits were having more time available and using natural environments as an alternative to gyms and organized sports. The most common motive for increased frequency of nature visits was "To be physically active". These findings suggest that nature visits provided important opportunities for physical activity during the COVID-19 crisis, but also that the mental health benefits of nature visits during such times may be under-communicated.